Underfill Material
The underfill material, composed of specific epoxy resins, functional compounds, and inorganic fillers, addresses the challenges of long filling times and thermal stress in large or multi-die semiconductor chip packages by enhancing fluidity and crack resistance.
Patent Information
- Application Number
- JP2023578458
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-01-18
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-01-18
AI Technical Summary
Large or multi-die semiconductor chip packages face challenges with long filling times for underfill materials and potential cracking due to thermal stress, requiring underfill materials with improved fluidity and crack resistance.
An underfill material comprising epoxy resins with multiple epoxy groups, a compound with functional and ethylenically unsaturated groups, and inorganic fillers, which reduces viscosity and enhances crack resistance, allowing for faster filling and improved thermal stability.
The underfill material achieves a short filling time and excellent crack resistance, ensuring efficient packaging of large or multi-die semiconductor chip packages while minimizing defects.
Smart Images

Figure 0007673842000003 
Figure 0007673842000004 
Figure 0007673842000005
Abstract
Description
[Technical field]
[0001] The present invention relates to an underfill material, a cured product of the underfill material, a semiconductor chip package including the cured product of the underfill material, a method for manufacturing the semiconductor chip package, and a semiconductor device including the semiconductor chip package. [Background technology]
[0002] Demand for semiconductor chip packages including a circuit board and a semiconductor chip mounted on the circuit board is increasing with the spread of smartphones, tablet PCs, etc. When joining a circuit board and a semiconductor chip, an insulating material called an underfill is filled into the gap (space) between the circuit board and the semiconductor chip in order to protect the joint and wiring from the external environment and to prevent defects such as cracks caused by differences in thermal expansion between the circuit board and the semiconductor chip.
[0003] There are two methods for filling the underfill material: a pre-application method, in which the underfill material is first applied to the circuit board and then bonded to the semiconductor chip, and a post-application method (capillary underfill method), in which the underfill material is filled into the gap after the circuit board and semiconductor chip are bonded.
[0004] As an underfill material used in the post-coating method, for example, an underfill material containing an epoxy resin and a curing agent has been disclosed (see Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2021-075508 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, in the cutting-edge semiconductor field, 900mm 2There is an increasing need for semiconductor chip packages such as the above-mentioned large die packages or multi-die packages having multiple dies.
[0007] However, when the package is large or has multiple dies, the post-coating method has the problem that it takes a long time to fill the gap between the circuit board and the semiconductor chip with underfill material.In addition, because the package is large, thermal stress can cause cracks in the underfill material.
[0008] Thus, underfill materials used in the post-coating method are required to have fluidity in order to shorten the filling time. In addition, cured underfill materials used in large die packages and multi-die packages are required to have excellent crack resistance and to suppress overflow around the die after filling with the underfill material, i.e., to reduce the area of the so-called fillet.
[0009] The present invention has been devised in view of the above-mentioned problems, and has an object to provide an underfill material that can be filled in a short time and gives a cured product that has excellent crack resistance; a cured product of the underfill material; a semiconductor chip package including the cured product of the underfill material; a semiconductor device including the semiconductor chip package; and a method for manufacturing the semiconductor chip package. [Means for solving the problem]
[0010] As a result of extensive investigations, the present inventors have found that the above problems can be solved by an underfill material having the following composition, and have completed the present invention.
[0011] That is, the present invention includes the following. [1] (A) an epoxy resin having two or more epoxy groups in one molecule; (B) a compound having an ethylenically unsaturated group and a functional group capable of reacting with the epoxy group of component (A), and (C) An underfill material containing an inorganic filler. [2] The underfill material according to [1], further comprising (D) a non-functional ethylenically unsaturated group-containing compound capable of reacting with component (A). [3] The underfill material according to [2], wherein the content of component (D) is 10% by mass or more and 70% by mass or less, assuming the resin component in the underfill material to be 100% by mass. [4] The underfill material according to any one of [1] to [3], wherein the content of component (C) is 60 mass % or more, relative to 100 mass % of the components of the underfill material. [5] The underfill material according to any one of [1] to [4], which has a viscosity of 2000 mPa.s or less at 40°C. [6] The underfill material according to any one of [1] to [5], wherein the molar ratio of all epoxy groups in component (A) to all functional groups in component (B) (total epoxy groups in component (A) : total functional groups in component (B)) is in the range of 30:70 to 80:20. [7] The underfill material according to any one of [1] to [6], wherein the functional group in component (B) that can react with the epoxy group in component (A) is one or more groups selected from an epoxy group, an acid anhydride group, and a carboxyl group. [8] The underfill material according to any one of [1] to [7], wherein component (B) contains a compound having one or more epoxy groups and one or more ethylenically unsaturated groups in one molecule. [9] The underfill material according to any one of [1] to [8], wherein the component (B) contains glycidyl (meth)acrylate.
[10] The underfill material according to any one of [1] to [9], further comprising (E) a radical polymerization catalyst.
[11] The underfill material according to any one of [1] to
[10] , further comprising (F) an organic base.
[12] The underfill material according to any one of [1] to
[11] , further comprising (G) an organic filler.
[13] The underfill material according to any one of [1] to
[12] , wherein the average particle size of component (C) is 15 μm or less.
[14] The underfill material according to any one of [1] to
[13] , wherein the cured product obtained by curing the underfill material has an elastic modulus of 1.0 GPa or more at 250°C.
[15] The underfill material according to any one of [1] to
[14] , wherein the cure shrinkage rate of the cured product obtained by curing the underfill material is 1% or more.
[16] The underfill material according to any one of [1] to
[15] , which is used to fill a gap between a circuit board and a semiconductor chip.
[17] The underfill material according to any one of [1] to
[16] , which is used to fill a gap between a semiconductor chip and a redistribution layer.
[18] The underfill material according to any one of [1] to
[17] , which is used to fill a gap between a circuit board and a rewiring layer.
[19] The underfill material according to
[17] or
[18] , wherein the redistribution layer comprises polyimide.
[20] The underfill material according to any one of [1] to
[19] , which is for use in a multi-die package semiconductor device.
[21] The area of a semiconductor chip package is 900 mm 2 The underfill material according to any one of [1] to
[20] , which is for the above semiconductor device.
[22] The underfill material according to any one of [1] to
[21] , which is for a semiconductor device including a fan-out package.
[23] The underfill material according to any one of [1] to
[22] , which is for a semiconductor device including a semiconductor package including a silicon interposer.
[24] The underfill material according to any one of [1] to
[23] , which is for a semiconductor device including a stack in which two or more semiconductor chips are stacked vertically through through-silicon vias.
[25] The underfill material according to any one of
[16] to
[18] , wherein the gap is 200 μm or less.
[26] The underfill material according to any one of
[16] to
[18] , wherein the gap is 100 μm or less.
[27] The underfill material according to any one of [1] to
[26] , which contains at least one component (D) having a viscosity at 25°C of 50 mPa.s or less.
[28] The underfill material according to any one of [1] to
[27] , which contains at least one component (B) having a viscosity at 25°C of 50 mPa.s or less.
[29] The underfill material according to any one of [1] to
[28] , which is an underfill material used in a post-coating method.
[30] A semiconductor chip package comprising a cured underfill material according to any one of [1] to
[29] .
[31] A semiconductor chip package comprising: a circuit board; a semiconductor chip bonded and mounted on the circuit board; and a cured product of the underfill material according to any one of [1] to
[29] that fills a gap between the circuit board and the semiconductor chip.
[32] The semiconductor chip package according to
[30] or
[31] , wherein when the projected area of the semiconductor chip surface is S1 and the projected area of the cured underfill material is S2, (S2 / S1) × 100 is 120% or less.
[33] The semiconductor chip package according to any one of
[30] to
[32] , wherein when the projected area of the semiconductor chip surface is S1 and the projected area of the cured underfill material is S2, (S2 / S1) × 100 is 110% or less.
[34] The semiconductor chip package according to any one of
[30] to
[33] , wherein when the projected area of the semiconductor chip surface is S1 and the projected area of the cured underfill material is S2, (S2 / S1) × 100 is 105% or less.
[35] The semiconductor chip package according to any one of
[30] to
[34] , wherein the cross-sectional shape of the cured underfill material becomes smaller from the semiconductor chip toward the center of the cured material and becomes larger from the center of the cured material toward the circuit board.
[36] A method for manufacturing a semiconductor chip package, comprising the step of filling a gap between a circuit board and a semiconductor chip or an interposer with the underfill material according to any one of [1] to
[29] , Semiconductor chip packages or interposers with an area of 900mm2 The above method for manufacturing a semiconductor chip package, wherein the time required to complete filling of the underfill material for a gap of 600 μm or less is less than 120 minutes.
[37] A semiconductor device comprising the semiconductor chip package according to any one of
[30] to
[36] .
[38] A cured product of the underfill material according to any one of [1] to
[29] . Effect of the Invention
[0012] According to the present invention, it is possible to provide an underfill material that can provide a cured product having excellent crack resistance with a short filling time; a cured product of the underfill material; a semiconductor chip package including the cured product of the underfill material; a semiconductor device including the semiconductor chip package; and a method for manufacturing the semiconductor chip package. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view and a top view showing an example of a semiconductor chip package according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing an example of the semiconductor chip package according to the first embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing an example of a semiconductor chip package according to a second embodiment of the present invention. [Figure 4] FIG. 4 is a cross-sectional view showing an example of a semiconductor chip package according to a third embodiment of the present invention. [Diagram 5] FIG. 5 is a cross-sectional view showing an example of a semiconductor chip package according to a fourth embodiment of the present invention. [Figure 6] FIG. 6 is a cross-sectional view showing an example of a semiconductor chip package according to a fifth embodiment of the present invention. [Figure 7] FIG. 7 is a cross-sectional view showing an example of a semiconductor chip package according to the sixth embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0015] [Underfill material] The underfill material of the present invention contains (A) an epoxy resin having two or more epoxy groups in one molecule, (B) a compound having a functional group and an ethylenically unsaturated group capable of reacting with the epoxy group of the (A) component, and (C) an inorganic filler. Such an underfill material has a low viscosity, so that the filling time is short and a cured product having excellent crack resistance can be obtained. In addition, the underfill material usually has low volatility, and it is also possible to obtain a cured product having excellent average linear thermal expansion coefficient (CTE) and glass transition temperature (Tg).
[0016] The underfill material may further contain optional components such as (D) a carboxyl group-free ethylenically unsaturated group-containing compound, (E) a radical polymerization catalyst, (F) an organic base, (G) an organic filler, (H) other additives, and (I) a solvent, as necessary. Each component contained in the underfill material will be described in detail below.
[0017] <(A) Epoxy resin having two or more epoxy groups in one molecule> The underfill material contains, as component (A), an epoxy resin having two or more epoxy groups in one molecule. The type of component (A) is not particularly limited as long as it can react with component (B) described below and harden. Among them, component (A) that does not contain an ethylenically unsaturated group is preferable. One type of component (A) may be used alone, or two or more types may be used in combination.
[0018] The component (A) contains an epoxy resin having two or more epoxy groups in one molecule, preferably three or more, and more preferably four or more. There is no particular upper limit, but it can be 10 or less, for example.
[0019] From the viewpoint of obtaining the effects of the present invention significantly, the component (A) is preferably an epoxy resin that is liquid at 25°C (hereinafter, also referred to as "liquid epoxy resin"). Therefore, in a preferred embodiment, the component (A) is liquid at 25°C. In the present invention, the term "liquid" for an epoxy resin means that the viscosity of the epoxy resin at 25°C is 30000 mPa·s or less, and the viscosity is preferably 25000 mPa·s or less, more preferably 20000 mPa·s or less, and even more preferably 15000 mPa·s or less, 10000 mPa·s or less, 8000 mPa·s or less, 6000 mPa·s or less, or 5000 mPa·s or less. A preferred embodiment of the component (A) is a liquid epoxy resin having two or more epoxy groups in one molecule.
[0020] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, hydrogenated bisphenol A type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred, and bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, and glycidyl amine type epoxy resin are more preferred.
[0021] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", and "825" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycilol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation; and "EP-4088S" (glycidylamine type epoxy resins) manufactured by ADEKA Corporation. Examples of epoxy resins include: "ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd. (a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); "EX-721" manufactured by Nagase ChemteX Corporation (glycidyl ester type epoxy resin); "Celloxide 2021P" manufactured by Daicel Corporation (alicyclic epoxy resin with an ester skeleton); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resin with a butadiene structure); "ZX1658" and "ZX1658GS" manufactured by Nippon Steel Chemical & Material Co., Ltd. (1,4-glycidylcyclohexane type epoxy resin), "YX8000" manufactured by Mitsubishi Chemical Corporation (hydrogenated bisphenol A type epoxy resin), and "KF-101" manufactured by Shin-Etsu Chemical Co., Ltd. (epoxy modified silicone resin).
[0022] The epoxy group equivalent of the (A) epoxy resin is preferably in the range of 50 g / eq. to 300 g / eq., and the upper limit is more preferably 250 g / eq. or less, further preferably 240 g / eq. or less, 220 g / eq. or less, 200 g / eq. or less, or 180 g / eq. or less. The epoxy group equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0023] From the viewpoint of significantly obtaining the desired effects of the present invention, the weight average molecular weight (Mw) of the (A) epoxy resin is preferably 100 to 5000, more preferably 250 to 3000, and further preferably 400 to 1500. The weight average molecular weight of the resin is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography (GPC).
[0024] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (A) epoxy resin, when the resin component in the underfill material is taken as 100 mass%, is preferably 5 mass% or more, more preferably 10 mass% or more, and even more preferably 15 mass% or more, and the upper limit is preferably 60 mass% or less, more preferably 55 mass% or less, and even more preferably 50 mass% or less.
[0025] In the present invention, the "resin component" of the underfill material refers to the components constituting the underfill material excluding the inorganic filler described below, and in cases where the underfill material contains an organic filler which is an optional component, the "resin component" refers to the components excluding the inorganic filler and the organic filler.
[0026] <(B) Compound Having a Functional Group Reactive with Component (A) and an Ethylenically Unsaturated Group> The underfill material contains, as component (B), a compound having a functional group and an ethylenically unsaturated group capable of reacting with component (A). By including component (B), the viscosity of the underfill material can be reduced, and a cured product can be obtained by reacting with component (A). Component (B) does not include those that fall under the above-mentioned component (A). Component (B) may be used alone or in combination of two or more types.
[0027] The (B) component has a functional group that can react with the (A) component. The functional group that can react with the (A) component is a group that can react with the epoxy group of the (A) component, and examples thereof include an epoxy group, an acid anhydride group, a carboxyl group, a hydroxyl group, an amino group, and an isocyanate group. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, one or more selected from an epoxy group, an acid anhydride group, a hydroxyl group are preferable, and one or more selected from an epoxy group, an acid anhydride group, and a carboxyl group are more preferable. The functional group that can react with the (A) component preferably has one functional group in one molecule, and may have two or more functional groups in one molecule. When two or more functional groups are present in one molecule, the functional groups that can react with the (A) component may be the same or different.
[0028] The (B) component has an ethylenically unsaturated group. The ethylenically unsaturated group refers to a group containing an ethylenically carbon-carbon unsaturated bond. The ethylenically unsaturated group is usually a monovalent group, and examples thereof include a vinyl group, an allyl group, a propargyl group, a butenyl group, an ethynyl group, a phenylethynyl group, a maleimide group, a nadiimide group, and a (meth)acryloyl group. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, a (meth)acryloyl group and a vinyl group are preferable, and a (meth)acryloyl group is more preferable. It is preferable that one or more ethylenically unsaturated groups are contained in one molecule, and a plurality of ethylenically unsaturated groups may be contained. When a plurality of ethylenically unsaturated groups are contained in one molecule, the ethylenically unsaturated groups may be the same or different. The (meth)acryloyl group includes a methacryloyl group, an acryloyl group, and a combination thereof.
[0029] The concentration of the functional group capable of reacting with component (A) is preferably 0.05 mmol / g or more, more preferably 0.1 mmol / g or more, and preferably 10 mmol / g or less, more preferably 5 mmol / g or less. For example, when the functional group is an epoxy group, the concentration of the epoxy group is determined from the epoxy equivalent obtained based on JIS K 7236-1995.
[0030] Examples of the component (B) include carboxyl group-containing monomers, acid anhydride group-containing monomers, epoxy group-containing monomers such as glycidyl group-containing monomers, hydroxy group-containing monomers, amino group-containing monomers, and isocyanate group-containing monomers.
[0031] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, succinic acid, cinnamic acid, and crotonic acid.
[0032] Examples of acid anhydride group-containing monomers include (meth)acrylic anhydride, maleic anhydride, succinic anhydride, itaconic anhydride, phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, and benzophenonetetracarboxylic dianhydride.
[0033] Examples of epoxy group-containing monomers include glycidyl (meth)acrylate, glycidyl 4-hydroxybutyl (meth)acrylate, and allyl glycidyl ether.
[0034] Examples of hydroxy group-containing monomers include 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, (4-hydroxymethyl)cyclohexylmethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2,2-dimethyl-2-hydroxyethyl (meth)acrylate, N-methylol (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide.
[0035] Examples of the amino group-containing monomer include dimethylaminoethyl (meth)acrylate and diethylaminoethyl (meth)acrylate.
[0036] An example of an isocyanate group-containing monomer is 2-(meth)acryloyloxyethyl isocyanate.
[0037] The term "(meth)acrylate" includes methacrylate, acrylate, and a combination thereof. Methacrylic acid and acrylic acid are sometimes collectively referred to as "(meth)acrylic acid."
[0038] Among them, from the viewpoint of obtaining the effect of the present invention remarkably, the (B) component is preferably one or more selected from a carboxyl group-containing monomer, an acid anhydride group-containing monomer, and an epoxy group-containing monomer, and more preferably a combination of an acid anhydride group-containing monomer and an epoxy group-containing monomer. As the acid anhydride group-containing monomer, (meth)acrylic anhydride is preferable, and as the epoxy group-containing monomer, a compound having one epoxy group and one or more ethylenically unsaturated groups in one molecule is preferable, and glycidyl (meth)acrylate is more preferable. Among them, from the viewpoint of obtaining the effect of the present invention remarkably, as the (B) component, it is preferable to use a combination of (meth)acrylic anhydride and glycidyl (meth)acrylate.
[0039] Component (B) may be a commercially available product. Specific examples of commercially available products of component (B) include "4HBAGE" manufactured by Mitsubishi Chemical Corporation and "Neoallyl G" manufactured by Osaka Soda Co., Ltd.
[0040] From the viewpoint of obtaining the effects of the present invention prominently, the viscosity of the (B) component at 25°C is preferably 1 Pa·s or less, more preferably 100 mPa·s or less, and even more preferably 50 mPa·s or less, or 10 mPa·s or less. The lower limit is not particularly limited, but may be, for example, 0.1 mPa·s or more, 0.3 mPa·s or more, or 1 mPa·s or more. The viscosity can be measured, for example, using a vibration viscometer. When two or more (B) components are included, it is preferable to include at least one (B) component having a viscosity of 50 mPa·s or less at 25°C.
[0041] The weight average molecular weight (Mw) of the component (B) is preferably 10-10,000, more preferably 20-5,000, even more preferably 30-1,000, and particularly preferably 50-500.
[0042] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of component (B) is preferably 10 mass % or more, more preferably 15 mass % or more, and even more preferably 20 mass % or more, and is preferably 60 mass % or less, more preferably 55 mass % or less, and even more preferably 50 mass % or less, based on 100 mass % of the resin component in the underfill material.
[0043] The molar ratio of all epoxy groups in component (A) to all functional groups in component (B) (total epoxy groups in component (A):total functional groups in component (B)) is preferably in the range of 30:70 to 80:20, more preferably in the range of 40:60 to 60:40. By incorporating components (A) and (B) in the underfill material in such a ratio, it becomes possible to obtain the effects of the present invention significantly.
[0044] <(C) Inorganic filler> The underfill material contains an inorganic filler (C) as component (C). Examples of the material for the inorganic filler (C) include silica, alumina, barium sulfate, talc, clay, mica powder, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum borate, barium titanate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, barium zirconate, and calcium zirconate. Among these, silica is preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. Moreover, spherical silica is preferred as the silica. The inorganic filler (C) may be used alone or in combination of two or more.
[0045] (C) inorganic fillers can be classified into (C-1) inorganic fillers with an average particle size exceeding 0.05 μm and (C-2) inorganic fillers with an average particle size of 0.05 μm or less. By including the (C-1) component in the underfill material, it is possible to improve the elastic modulus of the cured product of the underfill material. This can suppress warping of the cured product, and can further improve reflow resistance and crack resistance. In addition, by including the (C-2) component in the underfill material, it is possible to suppress settling of the components contained in the underfill material. The (C) inorganic filler may include the (C-2) component together with the (C-1) component. The (C) inorganic filler preferably includes either the (C-1) component or the (C-2) component, and more preferably includes both the (C-1) component and the (C-2) component.
[0046] From the viewpoint of obtaining the effects of the present invention significantly, the average particle size of the component (C-1) is preferably more than 0.05 μm, more preferably 0.1 μm or more, even more preferably 0.3 μm or more, or 1.0 μm or more, and is preferably 25 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less.
[0047] Commercially available products of component (C-1) include, for example, "UFP-30" (manufactured by Denka Kagaku Kogyo Co., Ltd.); "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", "SO-C1", and "SC-C2" (all manufactured by Admatechs Co., Ltd.); "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" (manufactured by Tokuyama Corporation), and the like.
[0048] From the viewpoint of obtaining the effects of the present invention prominently, the average particle size of the (C-2) component is preferably 0.05 μm or less, more preferably 0.03 μm or less, even more preferably 0.02 μm or less, and is preferably 0.001 μm or more, more preferably 0.003 μm or more, even more preferably 0.005 μm or more.
[0049] Commercially available products of the component (C-2) include, for example, Aerosil 200, Aerosil R805, and Aerosil RY300 (manufactured by Nippon Aerosil Co., Ltd.).
[0050] The average particle size of the inorganic filler (C) can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample is measured using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, and the volume-based particle size distribution of the inorganic filler (C) is measured using a flow cell method, and the average particle size can be calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0051] The inorganic filler is preferably one which has been surface-treated with a surface treatment agent such as an aminosilane coupling agent, a ureidosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a vinylsilane coupling agent, a styrylsilane coupling agent, an acrylate silane coupling agent, an isocyanate silane coupling agent, a sulfide silane coupling agent, an organosilazane compound, a titanate coupling agent, or an alkoxysilane to improve its moisture resistance and dispersibility.
[0052] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM22" (dimethyldimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM5783" (N-phenyl-3-aminooctyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), and Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent). Among them, nitrogen atom-containing silane coupling agents are preferred, phenyl group-containing aminosilane coupling agents are more preferred, and N-phenyl-3-aminoalkyltrimethoxysilane is even more preferred. The surface treatment agents may be used alone or in any combination of two or more in any ratio.
[0053] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the (C) inorganic filler. From the viewpoint of improving the dispersibility of the (C) inorganic filler, the amount of carbon per unit surface area of the (C) inorganic filler is preferably 0.02 mg / m 2 More preferably, 0.1 mg / m 2 More preferably, 0.2 mg / m 2On the other hand, from the viewpoint of suppressing an increase in the melt viscosity of the underfill material, the carbon amount is preferably 1 mg / m 2 Less than or equal to 0.8 mg / m 2 Less than 0.5 mg / m 2 The following is the result.
[0054] The amount of carbon per unit surface area of the (C) inorganic filler can be measured after the surface-treated (C) inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (hereinafter sometimes abbreviated as "MEK")). Specifically, a sufficient amount of methyl ethyl ketone is mixed with the (C) inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. Thereafter, the supernatant liquid is removed, and the solid content is dried, after which the amount of carbon per unit surface area of the (C) inorganic filler can be measured using a carbon analyzer. An "EMIA-320V" manufactured by Horiba, Ltd. can be used as the carbon analyzer.
[0055] The content of the inorganic filler (C) (the total content of the components (C-1) and (C-2)) is preferably 60% by mass or more, more preferably 65% by mass or more, even more preferably 70% by mass or more, 75% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less, 80% by mass or less, based on 100% by mass of the components in the underfill material. The underfill material of the present invention has a low viscosity because it contains the component (B) and, if necessary, the component (D) described below. Therefore, even if a large amount of the inorganic filler (C) is contained, the viscosity of the underfill material is maintained low. As a result, it is possible to improve the filling time and filling speed of the underfill material, and it is possible to obtain a cured product of the underfill material with a high elastic modulus. In addition, by increasing the elastic modulus, it is possible to suppress the occurrence of warping, and it is also possible to improve reflow resistance and crack resistance. The "components in the underfill material" refers to all components contained in the underfill material.
[0056] The content of component (C-1), relative to 100 mass% of the components in the underfill material, is preferably 60 mass% or more, more preferably 65 mass% or more, even more preferably 70 mass% or more or 75 mass% or more, and is preferably 95 mass% or less, more preferably 90 mass% or less, even more preferably 85 mass% or less or 80 mass% or less.
[0057] From the viewpoint of prominently obtaining the effects of the present invention, the content of the (C-2) component, when the resin component in the underfill material is taken as 100 mass%, is preferably 0.01 mass%, more preferably 0.05 mass% or more, and 0.1 mass% or more, and the upper limit is preferably 1.5 mass% or less, more preferably 1 mass% or less, and 0.5 mass% or less.
[0058] <(D) Compound containing no functional group and containing an ethylenically unsaturated group capable of reacting with component (A)> The underfill material may contain, as an optional component, (D) a functional group-free ethylenically unsaturated group-containing compound capable of reacting with component (A). By including component (D) in the underfill material, the viscosity of the underfill material can be reduced, making it possible to shorten the filling time. Component (D) does not include components (A) to (C) described above. Component (D) may be used alone or in combination of two or more types.
[0059] From the viewpoint of obtaining the effects of the present invention more significantly, the component (D) may be a compound having an ethylenically unsaturated group but not having a functional group capable of reacting with the component (A). The functional group capable of reacting with the component (A) and the ethylenically unsaturated group are as described above.
[0060] Examples of the component (D) include (meth)acrylic acid esters, aromatic unsaturated monomers such as styrene-based monomers, heterocycle-containing unsaturated monomers, and dienes.
[0061] Examples of (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, octyl (meth)acrylate, lauryl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, cyclododecyl (meth)acrylate, and phenoxyethylene glycol (meth)acrylate.
[0062] As the aromatic unsaturated monomer, a compound containing an aromatic ring and an ethylenic carbon-carbon unsaturated bond can be used, and examples thereof include styrene, α-methylstyrene, 4-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methoxystyrene, pt-butylstyrene, pn-butylstyrene, p-tert-butoxystyrene, 2-hydroxymethylstyrene, 2-chlorostyrene, 4-chlorostyrene, 2,4-dichlorostyrene, 1-vinylnaphthalene, divinylbenzene, 2-acetoxystyrene, 3-acetoxystyrene, 4-acetoxystyrene, 4-vinylphenylbenzoate, p-styrenesulfonic acid or an alkali metal salt thereof (sodium salt, potassium salt, etc.).
[0063] Examples of heterocycle-containing unsaturated monomers include 2-vinylthiophene, N-methyl-2-vinylpyrrole, 1-vinyl-2-pyrrolidone, 2-vinylpyridine, and 4-vinylpyridine.
[0064] Examples of dienes include α-olefins such as 1-hexene, 1-octene, and 1-decene; butadiene, isoprene, 4-methyl-1,4-hexadiene, and 7-methyl-1,6-octadiene.
[0065] Of these, from the viewpoint of achieving the effects of the present invention more significantly, the component (D) is preferably at least one selected from (meth)acrylic acid esters and aromatic unsaturated monomers (styrene-based monomers).
[0066] The component (D) may be a commercially available product, such as "PHE-1G" (phenoxyethylene glycol methacrylate) manufactured by Nakamura Chemical Co., Ltd., "Light Ester BZ" (benzyl methacrylate) manufactured by Kyoeisha Chemical Co., Ltd., and "Light Ester IB-X" (isobornyl methacrylate) manufactured by Kyoeisha Chemical Co., Ltd.
[0067] From the viewpoint of obtaining the effects of the present invention prominently, the viscosity of the (D) component at 25°C is preferably 1 Pa·s or less, more preferably 100 mPa·s or less, and even more preferably 50 mPa·s or less. There is no particular limitation on the lower limit, but it can be, for example, 0.1 mPa·s or more, 0.2 mPa·s or more, or 0.3 mPa·s or more. The viscosity can be measured, for example, using a vibration viscometer. When two or more types of (D) components are included, it is preferable to include at least one (D) component having a viscosity of 50 mPa·s or less at 25°C.
[0068] The weight average molecular weight (Mw) of the component (D) is preferably 10-10,000, more preferably 20-5,000, even more preferably 30-1,000, and particularly preferably 50-500.
[0069] From the viewpoint of significantly obtaining the desired effects of the present invention, the content of component (D) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 55% by mass or less, and 50% by mass or less, based on 100% by mass of the resin component in the underfill material.
[0070] When the content of the resin component (D) is taken as 100% by mass, D1, and the content of the resin component (B) is taken as 100% by mass, B1 is taken as B1 / D1, which is preferably 0.1 or more, more preferably 0.5 or more, even more preferably 0.8 or more, or 1 or more, and is preferably 5 or less, more preferably 3 or less, or even more preferably 2 or less, 1.9 or less, or 1.8 or less. By adjusting the contents of the components (B) and (D) so that B1 / D1 is within this range, it is possible to obtain the effects of the present invention significantly.
[0071] <(E) Radical Polymerization Catalyst> The underfill material may further contain (E) a radical polymerization catalyst as an optional component. By containing (E) a radical polymerization catalyst, the reaction of components (B) and (D) when curing the underfill material can be promoted, and the curing time and curing temperature can be efficiently adjusted. Component (E) does not include components (A) to (D) described above. Component (E) may be used alone or in combination of two or more types.
[0072] As the (E) radical polymerization catalyst, it is preferable to use a thermal radical polymerization catalyst which generates radicals by applying thermal energy.
[0073] Examples of the thermal radical polymerization catalyst include dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, and t-hexylperoxy-2-ethylhexanoate; diacyl peroxides such as lauroyl peroxide, benzoyl peroxide, benzoyltoluyl peroxide, and toluyl peroxide; peroxyesters such as t-butyl peracetate, t-butyl peroxyoctoate, and t-butyl peroxybenzoate; ketone peroxides; peroxycarbonates; peroxyketals such as 1,1-di(t-amylperoxy)cyclohexane; 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(isobutyronitrile), and 2,2'-azobis(2-methylbutyronitrile). azonitrile compounds such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}; azoamidine compounds such as 2,2'-azobis(2-amidinopropane) dihydrochloride and 2,2'-azobis[2-(2-imidazolin-2-yl)propane] dihydrochloride; azoalkane compounds such as 2,2'-azobis(2,4,4-trimethylpentane) and 4,4'-azobis(4-cyanopentanoic acid); azo compounds having an oxime skeleton such as 2,2'-azobis(2-methylpropionamide oxime), and azo compounds such as dimethyl 2,2'-azobis(isobutyrate), and the like. The thermal radical polymerization catalyst may be used alone or in combination of two or more. Among the above radical polymerization catalysts, dialkyl peroxides, diacyl peroxides, peracid esters, ketone peroxides, peroxycarbonates, and peroxyketals are collectively referred to as "peroxide radical polymerization catalysts."
[0074] As the (E) radical polymerization catalyst, it is preferable to use a peroxide-based thermal radical polymerization catalyst, from the viewpoint of obtaining the remarkable effects of the present invention.
[0075] The content of the (E) radical polymerization catalyst, relative to 100 mass% of the resin component in the underfill material, is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, or 0.3 mass% or more, and is preferably 3 mass% or less, more preferably 2 mass% or less, 1.8 mass% or less, 1.5 mass% or less, or 1 mass% or less.
[0076] <(F) Organic Base> The underfill material may further contain an organic base (F) as an optional component. By containing the organic base (F), the reaction between the components (A) and (B) can be promoted when the underfill material is cured, and the curing time and curing temperature can be efficiently adjusted. The component (F) does not include components (A) to (E) described above. The component (F) may be used alone or in combination of two or more types.
[0077] As the (F) organic base, it is preferable to use at least one type selected from amine-based curing accelerators, organic phosphorus-based curing accelerators, and imidazole-based curing accelerators that are conventionally known as curing accelerators for epoxy resins.
[0078] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.
[0079] The organic phosphorus curing accelerator is preferably at least one selected from the group consisting of phosphonium salts and phosphines.
[0080] Examples of the phosphonium salt include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, and the like. Examples of aromatic phosphonium salts include aromatic phosphonium salts such as phenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate, tetraphenylphosphonium tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate.
[0081] Examples of phosphines include aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine; dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, and tris(2,5-dimethylphenyl)phosphine. tris(2,6-dimethylphenyl)phosphine, tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2- Examples of aromatic phosphines include bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; and aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct.
[0082] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.
[0083] The content of the (F) organic base, relative to 100 mass% of the resin component in the underfill material, is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, or 0.3 mass% or more, and is preferably 3 mass% or less, more preferably 2 mass% or less, 1.8 mass% or less, 1.5 mass% or less, or 1 mass% or less.
[0084] <(G)Organic filler> The underfill material may further contain an organic filler (G) as an optional component. The component (G) does not include components (A) to (F) described above. By including the component (G) in the underfill material, it is possible to suppress settling of the components contained in the underfill material. The component (G) may be used alone or in combination of two or more types.
[0085] Component (G) is present in the underfill material in particulate form, and is usually included in the cured product while maintaining its particulate form. Component (G) may be any organic filler that can be used when forming insulating materials for electronic components such as semiconductor chip packages and printed wiring boards, and examples of such fillers include rubber particles, polyamide fine particles, silicone particles, LCP powder, and PPS powder.
[0086] The rubber particles are not particularly limited as long as they are fine particles of resin that is insoluble and infusible in organic solvents by chemically crosslinking a resin that exhibits rubber elasticity, and examples of such fine particles include hollow polymer particles, acrylonitrile butadiene rubber particles, butadiene rubber particles, acrylic rubber particles, etc. Specific examples of rubber particles include XER-91 (manufactured by Japan Synthetic Rubber Co., Ltd.), Staphyloid AC3355, AC3816, AC3816N, AC3832, AC4030, AC3364, IM101 (all manufactured by Aica Kogyo Co., Ltd.), Paraloid EXL2655, EXL2602 (all manufactured by Dow Chemical Co., Ltd.), etc.
[0087] The average particle diameter of the organic filler is preferably in the range of 0.005 μm to 100 μm, more preferably in the range of 0.2 μm to 15 μm. The average particle diameter of the organic filler can be measured using a dynamic light scattering method. For example, the organic filler is uniformly dispersed in a suitable organic solvent by ultrasonic waves or the like, and a particle size distribution of the organic filler is created on a mass basis using a concentrated particle size analyzer (Otsuka Electronics Co., Ltd.'s "FPAR-1000"), and the median diameter is taken as the average particle diameter.
[0088] The content of the (G) organic filler, when the components in the underfill material are taken as 100 mass%, is preferably 0.5 mass%, and more preferably 1 mass% or more, 1.5 mass% or more, or 1.8 mass% or more, and the upper limit is preferably 10 mass% or less, and more preferably 8 mass% or less, 6 mass% or less, or 5 mass% or less.
[0089] <(H) Optional Additives> The underfill material of the present invention may further contain any additives as long as they do not impair the effects of the present invention. Examples of such additives include thermosetting resins other than component (A); thermoplastic resins; epoxy resin curing agents such as phenol-based curing agents, benzoxazine-based curing agents, acid anhydride-based curing agents, cyanate ester-based curing agents, and active ester-based curing agents; organometallic compounds such as organocopper compounds, organozinc compounds, and organocobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone-based leveling agents and acrylic polymer-based leveling agents; thickeners such as bentone and montmorillonite; defoamers such as silicone-based defoamers, acrylic-based defoamers, fluorine-based defoamers, and vinyl resin-based defoamers; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; and urea silanes. Examples of the additives include adhesion improvers, adhesion improvers such as triazole-based adhesion improvers, tetrazole-based adhesion improvers, and triazine-based adhesion improvers, antioxidants such as hindered phenol-based antioxidants, fluorescent brighteners such as stilbene derivatives, surfactants such as fluorine-based surfactants and silicone-based surfactants, flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, and red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide), and dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants, and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. The content of such additives may be determined according to the properties required for the underfill material.
[0090] <(I) Organic Solvent> The underfill material of the present invention may further contain an organic solvent as a volatile component. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, and diphenyl ether; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of the organic solvent include ether ester solvents such as ethyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate; ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butyl carbitol); amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; sulfoxide solvents such as dimethyl sulfoxide; nitrile solvents such as acetonitrile and propionitrile; aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The organic solvent may be used alone or in combination of two or more.
[0091] Since the underfill material of the present invention contains a combination of components (A) and (B), it is possible to reduce the viscosity even when the content of the organic solvent is low or when the underfill material does not contain an organic solvent. Therefore, the content of the organic solvent in the underfill material of the present invention may be reduced to, for example, 5% by mass or less, 4% by mass or less, 2% by mass or less, 1% by mass or less, or 0.5% by mass or less, or may be 0% by mass (solvent-free system).
[0092] The underfill material can be prepared by appropriately mixing the necessary components among the above-mentioned components, and kneading or mixing them as necessary using kneading means such as a triple roll mill, ball mill, bead mill, or sand mill, or stirring means such as a super mixer or planetary mixer.
[0093] <Physical properties of underfill material> The underfill material contains the component (B) and, if necessary, the component (D), so that even if the content of the inorganic filler (C) is high, it has a low viscosity at 40°C and is excellent in fluidity. Therefore, even in a large multi-die package, the filling speed of the underfill material is fast and the filling time of the underfill material can be shortened. The viscosity of the underfill material at 40°C is preferably 2000 mPa·s or less, more preferably 1500 mPa·s or less, further preferably 1000 mPa·s or less, 700 mPa·s or less, 500 mPa·s or less, 400 mPa·s or less, or 300 mPa·s or less. There is no particular lower limit, but it may be 1 mPa·s or more, 10 mPa·s or more, etc. The viscosity of the underfill material can be measured by the method described in the examples below.
[0094] The underfill material has a characteristic of being fast to fill because of its low viscosity. Therefore, when filling the gap between the circuit board and the semiconductor chip with the underfill material, the filling speed of the underfill material can be improved. The filling speed is preferably 5 mm / 1 min or more, more preferably 8 mm / 1 min or more, and even more preferably 10 mm / 1 min or more, 15 mm / 1 min or more. There is no particular upper limit, but it may be 100 mm / 1 min or less. The filling speed can be measured by the method described in the examples below.
[0095] The underfill material has a low viscosity and therefore a fast filling speed. Therefore, when filling the gap between the circuit board and the semiconductor chip with the underfill material, the filling speed of the underfill material can be improved. For example, when the area of the gap is 900 cm 2 A test module having a gap of 100 μm is prepared. This test module is heated, and the underfill material is dropped using a syringe. At this time, the time required for the filling to be completed (filling time) is preferably less than 120 min, more preferably 100 min or less, and even more preferably 50 min or less, 40 min or less, 30 min or less, or 25 min or less. There is no particular upper limit, but it may be 1 min or more. The filling speed can be measured by the method described in the examples below.
[0096] The cured product of the underfill material cured at 100°C for 5 hours exhibits the characteristic of a high elastic modulus at 250°C. Therefore, a cured product with excellent crack resistance can be obtained. The elastic modulus of the cured product of the underfill material at 250°C is preferably 1.0 GPa or more, more preferably 1.5 GPa or more, and even more preferably 2.0 GPa or more, 2.5 GPa or more. There is no particular upper limit, but it may be 10 GPa or less. The elastic modulus can be measured by the method described in the examples below.
[0097] A cured product obtained by curing an underfill material at 100°C for 5 hours usually exhibits the characteristic of having a high glass transition temperature (Tg). The glass transition temperature is preferably 150°C or higher, more preferably 155°C or higher, and even more preferably 160°C or higher or 180°C or higher. There is no particular upper limit, but it may be 300°C or lower. The glass transition temperature can be measured by the method described in the examples below.
[0098] The cured product obtained by curing the underfill material at 100°C for 5 hours exhibits the characteristic of a large cure shrinkage rate. Therefore, a cured product with excellent crack resistance can be obtained. The cure shrinkage rate is preferably 1% or more, more preferably 2% or more, and even more preferably 3% or more. There is no particular lower limit, but it may be 25% or less. The cure shrinkage rate can be measured by the method described in the examples below.
[0099] A cured product obtained by curing an underfill material at 100°C for 5 hours usually exhibits the characteristic of a low average linear thermal expansion coefficient (CTE). Therefore, a cured product with excellent crack resistance can be obtained. The average linear thermal expansion coefficient from the glass transition temperature (Tg)+40°C to 260°C is preferably 100 ppm or less, more preferably 75 ppm or less, and even more preferably 50 ppm or less, less than 50 ppm. The lower limit is not particularly limited, but may be 1 ppm or more. The average linear thermal expansion coefficient can be measured according to the method described in the examples below.
[0100] The underfill material exhibits the characteristic of low volatility. Therefore, it is useful as an underfill material used in a post-coating method (capillary underfill method), and exhibits the characteristic of being able to obtain a cured product with excellent crack resistance. Volatility is measured by weighing out 1 g of the underfill material and placing it on a hot plate heated to 40°C for 1 hour. The weight loss rate at that time is preferably less than 10%, more preferably 7% or less, and even more preferably 4% or less, less than 4%. The lower limit is not particularly limited, but may be 0.01% or more. Volatility can be measured according to the method described in the examples below.
[0101] The underfill material of the present invention can be suitably used as an underfill material used to fill the gap between a circuit board and a semiconductor chip, and can be suitably used as an underfill material used in a post-application method (capillary underfill method). The underfill material of the present invention can also be suitably used as an underfill material used to fill the gap between a rewiring layer and a semiconductor chip, and the gap between a circuit board and a rewiring layer. For example, the underfill material of the present invention can be used as an underfill material for semiconductor devices including multi-die packages (underfill material used in semiconductor devices including multi-die packages), and as an underfill material for semiconductor chip packages having an area of 900 mm 2 Underfill material for semiconductor device (area 900mm or more) 2 The above-mentioned underfill material can be used for a wide range of required applications, such as an underfill material for semiconductor devices including a semiconductor chip package (underfill material for use in semiconductor devices including a fan-out package), an underfill material for semiconductor devices including a semiconductor package including a silicon interposer (underfill material for use in semiconductor devices including a semiconductor package including a silicon interposer), and an underfill material for semiconductor devices including two or more semiconductor chips overlapping vertically through through silicon vias (underfill material for use in semiconductor devices including a semiconductor chip package including two or more semiconductor chips overlapping vertically through through silicon vias).
[0102] [Cured product] The cured product of the present invention is obtained by curing the underfill material of the present invention. This cured product is usually obtained by thermally curing the underfill material. When the underfill material is thermally cured, volatile components such as component (I) are usually removed, but components such as components (A) to (H) are not removed. Therefore, the cured product may contain components such as components (A) to (H) or their reaction products. The curing conditions of the underfill material described below may be used as the curing conditions. In addition, the underfill material may be preheated before curing, and heating may be performed multiple times including preheating.
[0103] [Semiconductor chip package and its manufacturing method] The semiconductor chip package of the present invention includes the cured underfill material of the present invention. 2 There is an increasing need for semiconductor chip packages such as the above-mentioned large die packages or multi-die packages having multiple dies. The underfill material of the present invention has low viscosity and therefore excellent flowability. Therefore, it is possible to improve the filling speed of the underfill material.
[0104] The area of the large die package or semiconductor chip package is preferably 900 mm 2 More preferably, it is 1000 mm 2 More preferably, 1500 mm 2 That's all. There is no upper limit, but 5000mm 2 It could be the following etc.
[0105] As shown in Figures 1 and 2, the semiconductor chip package 1 of the present invention includes a circuit board 10, a semiconductor chip 30 bonded and mounted on the circuit board 10, and a cured product 20 of the underfill material of the present invention that fills the gap between the circuit board 10 and the semiconductor chip 30. The area of the semiconductor chip 30 is 900 mm2. 2 Thus, the preferred range for the area of the semiconductor chip 30 is the same as the area of the large die package.
[0106] The projected area S1 (mm 2 ), and the projected area of the surface of the cured underfill material 20 opposite to the circuit board side (sometimes referred to as the "projected area of the cured underfill material") S2 (mm 2), (S2 / S1)×100 is preferably 120% or less, more preferably 110% or less, more preferably 105% or less, and is preferably 80% or more, more preferably 85% or more, and further preferably 90% or more. By setting (S2 / S1)×100 within this range, the area of the fillet can be reduced, and the effect of improving crack resistance can be obtained.
[0107] 2, the cross-sectional shape of the cured underfill material 20 may be a so-called hollow shape, which is a shape that becomes smaller from the semiconductor chip 30 toward the center of the cured material 20 and becomes larger from the center of the cured material 30 toward the circuit board 10. The hollow shape of the cured underfill material provides an effect of improving crack resistance.
[0108] The semiconductor chip package can be manufactured, for example, by a method using the underfill material of the present invention, which includes the following step (2), and may also include the following steps (1) and (3) as necessary. (1) bonding a semiconductor chip to a circuit board; (2) filling a gap between a circuit board and a semiconductor chip or an interposer with the underfill material of the present invention; and (3) Hardening the underfill material
[0109] The steps (1) to (3) are preferably carried out in the order of step (1), step (2) and step (3).
[0110] <Process (1)> In step (1), a semiconductor chip is bonded to a circuit board. The circuit board may be a conventional circuit board used for forming a semiconductor chip package. The circuit board may have either a conductor layer or an insulating layer on one or both sides, and either the conductor layer or the insulating layer may be patterned.
[0111] The circuit board and the semiconductor chip can be bonded to each other by, for example, forming bumps on the circuit board or the semiconductor chip. The bumps may be formed according to a method known to those skilled in the art and used in the manufacture of semiconductor chip packages.
[0112] The bonding conditions for the circuit board and the semiconductor chip may be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board, such as the conditions used in flip-chip mounting of the semiconductor chip.
[0113] An example of the bonding method is a method of bonding a semiconductor chip to a circuit board. The bonding temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the bonding time is usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds). Another example of the bonding method is a method of placing a semiconductor chip on a circuit board and bonding it by reflow. The reflow conditions may be in the range of 120°C to 300°C.
[0114] <Process (2)> In step (2), the gap between the circuit board and the semiconductor chip is filled with the underfill material of the present invention. More specifically, after the semiconductor chip is bonded to the circuit board, the gap between the semiconductor chip and the circuit board is filled with the underfill material of the present invention. As described above, the underfill material of the present invention has a low viscosity, so that the filling speed can be improved. The gap is preferably 600 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less. The lower limit is not particularly limited, but may be 1 μm or more, for example.
[0115] The filling speed of the underfill material is 5 mm / 1 min or more, preferably 8 mm / 1 min or more, more preferably 10 mm / 1 min or more, and even more preferably 15 mm / 1 min or more. There is no particular upper limit, but it may be 100 mm / 1 min or less. The filling speed can be measured by the method described in the examples below.
[0116] The time required for filling the underfill material is, for example, 900 mm2 of semiconductor chip package. 2 When the gap is 100 μm, the time is less than 120 min, preferably 100 min or less, more preferably 50 min or less, and even more preferably 40 min or less, 30 min or less, or 25 min or less. There is no particular upper limit, but it may be 1 min or more. The filling completion time can be measured by the method described in the examples below.
[0117] One method of filling the underfill material is to discharge the underfill material near the side edge of the semiconductor chip and use capillary action to fill the gap between the semiconductor chip and the circuit board with the underfill material.
[0118] <Process (3)> In step (3), the underfill material is cured to obtain a cured product of the underfill material in the gap between the circuit board and the semiconductor chip. The curing conditions of the underfill material are not particularly limited, and the conditions usually adopted in forming an insulating layer of a printed wiring board may be used.
[0119] The thermal curing conditions for the underfill material vary depending on the type of underfill material, but in one embodiment, for example, the curing temperature is preferably 50° C. to 250° C., more preferably 60° C. to 240° C., and even more preferably 100° C. to 200° C. The curing time is preferably 5 minutes to 600 minutes, more preferably 10 minutes to 500 minutes, and even more preferably 15 minutes to 400 minutes.
[0120] Before the underfill material is thermally cured, the underfill material may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the underfill material, the underfill material may be preheated at a temperature of 40°C to 120°C, preferably 50°C to 115°C, more preferably 60°C to 110°C for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0121] As another embodiment (second embodiment), as shown in Fig. 3, a semiconductor chip package 100 of the present invention is a multi-die package including a circuit board 11, a plurality of semiconductor chips 31 bonded onto the circuit board 11 via bumps 41, and a cured product 21 of the underfill material of the present invention that fills the gaps between the circuit board 11 and the plurality of semiconductor chips 31. Since the underfill material of the present invention has a low viscosity, the filling speed of the underfill material can be improved even in a multi-die package having a plurality of semiconductor chips. The shapes of the circuit board and the cured product of the underfill material used in the second embodiment are the same as those in the first embodiment.
[0122] Another embodiment (third embodiment) is a fan-out type package. As shown in FIG. 4, the fan-out type package 200 includes a circuit board 12, a semiconductor chip 32 bonded to the circuit board 12 via bumps 42, a cured product 22 of the underfill material of the present invention filling the gap between the circuit board 12 and the semiconductor chip 32, and a sealing layer 51 formed to cover the periphery of the semiconductor chip 32. Since the underfill material of the present invention has a low viscosity, the filling speed of the underfill material can be improved even in a large fan-out type package. The shapes of the circuit board and the cured product of the underfill material used in the third embodiment are the same as those in the second embodiment. The insulating material used in the sealing layer may be the underfill material of the present invention or a known insulating material.
[0123] Usually, the insulating material used for the sealing layer contains a large amount of inorganic filler. Therefore, if the amount of inorganic filler contained in the underfill material is small, cracks may occur at the interface between the cured product of the underfill material and the sealing layer. The underfill material of the present invention exhibits the characteristic of low viscosity even if the content of inorganic filler is increased. Therefore, by increasing the amount of inorganic filler contained in the underfill material of the present invention, it is possible to suppress the occurrence of cracks at the interface with the sealing layer.
[0124] As another embodiment (fourth embodiment), as shown in FIG. 5, a semiconductor chip package 300 of the present invention includes a circuit board 13, a rewiring layer 61 bonded to the circuit board 13 via bumps 43, a semiconductor chip 33 bonded to the rewiring layer 61 via bumps 44, and cured products 23a and 23b of the underfill material of the present invention that fill the gap between the circuit board 13 and the rewiring layer 61 and the gap between the rewiring layer 61 and the semiconductor chip. The fourth embodiment may have a plurality of semiconductor chips as shown in FIG. 5, and may have bumps 49 on the surface of the circuit board 13 opposite to the surface on the semiconductor chip 33 side. The circuit board and the like used in the fourth embodiment are the same as those in the third embodiment. The cured products 23a and 23b of the underfill material may be the same underfill material or different underfill materials.
[0125] The rewiring layer is formed, for example, by laminating a resin layer containing polyimide resin, a conductor layer, and a resin layer containing polyimide resin in this order from the circuit board side. The material of the conductor layer includes one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin, and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (for example, nickel-chromium alloys, copper-nickel alloys, and copper-titanium alloys). Among these, from the viewpoints of versatility of conductor layer formation, cost, ease of patterning, etc., a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred. The resin layer containing a polyimide resin may be provided with via holes (not shown) as necessary, and electrically connected to the semiconductor chip and the circuit board through the vias.
[0126] Since the underfill material of the present invention has a low viscosity, the filling speed of the underfill material can be improved even in the package of the fourth embodiment. In addition, since the underfill material of the present invention has excellent affinity with polyimide, the adhesive strength between polyimide and the cured product of the underfill material can be improved. Therefore, even if the underfill material of the present invention is filled in the gap between the circuit board and the rewiring layer and the gap between the rewiring layer and the semiconductor chip, it is possible to suppress peeling at the interface between the rewiring layer and the cured product of the underfill material. The shapes of the circuit board and the cured product of the underfill material used in the fourth embodiment are the same as those in the third embodiment.
[0127] As another embodiment (fifth embodiment), as shown in FIG. 6, a semiconductor chip package 400 of the present invention includes a circuit board 14, a silicon interposer 80 bonded to the circuit board 14 via bumps 45, a semiconductor chip 34 bonded to the silicon interposer 80 via bumps 46, and cured products 24a and 24b of the underfill material of the present invention that fill the gap between the circuit board 14 and the silicon interposer 80 and the gap between the silicon interposer 80 and the semiconductor chip 34. The silicon interposer 80 may have a via hole 71 formed therein from the viewpoint of electrically connecting the circuit board 14 and the semiconductor chip 34. The fifth embodiment may have a plurality of semiconductor chips 34 as shown in FIG. 6. The cured products 24a and 24b of the underfill material may be the same underfill material or different underfill materials. Since the underfill material of the present invention has a low viscosity, the filling speed of the underfill material can be improved even in the package of the fifth embodiment. The shapes of the circuit board and the cured product of the underfill material used in the fifth embodiment are the same as those in the fourth embodiment.
[0128] The area of the silicon interposer is the same as that of the semiconductor chip package, and is preferably 900 mm 2 More preferably, it is 1000 mm 2 More preferably, 1500 mm 2That's all. There is no upper limit, but 5000mm 2 It could be the following etc.
[0129] As another embodiment (sixth embodiment), as shown in FIG. 7, a semiconductor chip package 500 of the present invention includes a circuit board 15, a silicon interposer 81 bonded to the circuit board 15 via bumps 47, a first semiconductor chip 35 bonded to the silicon interposer 81 via bumps 48, a stack 36 formed by stacking two or more semiconductor chips in the vertical direction, and cured products 25a and 25b of the underfill material of the present invention filling the gap between the circuit board 15 and the silicon interposer 81, and the gap between the silicon interposer 81 and the first semiconductor chip 35 and the stack 36. The stack 36 is composed of two or more layers of semiconductor chips, and the semiconductor chips are electrically connected through through silicon pillars 37. In addition, the silicon interposer 81 may have via holes 72 formed therein from the viewpoint of electrically connecting the circuit board 15, the semiconductor chip 35, and the stack 36. Since the underfill material of the present invention has a low viscosity, the filling speed of the underfill material can be improved even in the package of the sixth embodiment. The cured underfill materials 25a and 25b may be the same or different underfill materials. The shape of the circuit board and the cured underfill material used in the sixth embodiment are the same as those in the fifth embodiment.
[0130] [Semiconductor Devices] The semiconductor device of the present invention includes the semiconductor chip package of the present invention. The semiconductor device of the present invention can be manufactured using the semiconductor chip package of the present invention.
[0131] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES
[0132] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions are room temperature (25°C) and atmospheric pressure (1 atm).
[0133] <Example 1: Preparation of underfill material 1> 9.0 parts of a mixed resin of bisphenol A type epoxy resin and bisphenol F type epoxy resin ("ZX-1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy group equivalent of approximately 160-170g / eq.), 5.0 parts of methacrylic acid, and 6.0 parts of styrene were added and stirred. 80 parts of inorganic filler 1 (silica with average particle size of 8μm and maximum particle size of 25μm) were added, and 0.4 parts of an organic base (2E4MZ, 2-ethyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd.) and 0.1 parts of a radical polymerization catalyst ("Perhexyl O" manufactured by NOF Corporation) were added and uniformly dispersed in a high-speed rotating mixer to prepare underfill material 1.
[0134] <Examples 2 to 18 and Comparative Example 1: Preparation of Underfill Materials 2 to 19> In Example 1, the components were mixed in the mixing ratios shown in the table below, and a resin varnish was prepared using a high-speed rotating mixer. Underfill materials 2 to 19 were prepared in the same manner as in Example 1, except for the above points.
[0135] [Table 1]
[0136] The abbreviations in the table are as follows: The viscosity of each material was measured at a temperature of 25±2°C using a vibration viscometer ("VM-10A-L" manufactured by Sekonic Corporation). Component (A) ·ZX-1059: Manufactured by Nippon Steel Chemical & Material Co., Ltd., a mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin, epoxy equivalent 160~170g / eq. 828EL: Mitsubishi Chemical Corporation, bisphenol A type epoxy resin, epoxy equivalent 184~194g / eq. HP-4032SS: DIC Corporation, naphthalene type epoxy resin, epoxy equivalent 136~148g / eq. 630: Mitsubishi Chemical Corporation, glycidylamine type epoxy resin, epoxy equivalent 90-105g / eq. (B) Component Methacrylic acid: Tokyo Chemical Industry Co., Ltd., carboxyl group equivalent: 86g / eq. Viscosity: 1.3mPa.s ·SA: Manufactured by Shin Nakamura Chemical Co., Ltd., carboxyl group equivalent: 230 g / eq. Viscosity: 157 mPa.s Methacrylic anhydride: Tokyo Chemical Industry Co., Ltd., acid anhydride equivalent: 154g / eq. GMA: Glycidyl methacrylate, manufactured by Mitsubishi Gas Chemical Co., Ltd., epoxy equivalent 142g / eq. viscosity 2.0mPa.s 4HBAGE: 4-Hydroxybutyl acrylate glycidyl ether, manufactured by Mitsubishi Chemical, epoxy equivalent 200g / eq. viscosity 7.2mPa.s (C) Component Inorganic filler 1: Silica with average particle size of 8 μm and maximum particle size of 25 μm R805: Silica with an average particle size of 12 nm, treated with octylsilane, manufactured by Nippon Aerosil Co., Ltd. (D) Component Styrene: Tokyo Chemical Industry Co., Ltd., viscosity 0.7 mPa.s PHE-1G: Phenoxyethylene glycol methacrylate, manufactured by Shin-Nakamura Chemical Co., Ltd., viscosity 7.0 mPa.s (E) Component Perhexyl O: Radical polymerization catalyst, NOF Corporation Ingredient (F) 2E4MZ: Organic base, 2-ethyl-4-methylimidazole, manufactured by Shikoku Chemical Industry Co., Ltd. (G) Component ·LCP powder: average particle size 10μm PPS powder: average particle size 10μm (H) Component HN-2200: 3 or 4-Methyl-1,2,3,6-tetrahydrophthalic anhydride, Showa Denko Materials Co., Ltd., anhydrous equivalent weight 166g / eq. Content of component (C-1): Content of component (C-1) when the components in the underfill material are taken as 100 mass% Content of component (G): Content of component (G) when the components in the underfill material are taken as 100 mass%
[0137] <Viscosity measurement> The viscosity of each underfill material was measured at 40°C and 20 rpm using a viscosity / viscoelasticity measuring device (HAAKE Rheo Stress 6000 (manufactured by Thermo Scientific)) and evaluated according to the following criteria. ○: Viscosity is less than 700mPa.s △: Viscosity is 700mPa.s or more and 2000mPa.s or less ×: Viscosity exceeds 2000 mPa.s
[0138] <Preparation of cured product> A casting plate was prepared by sandwiching a silicon tube as a spacer between aluminum plates coated with a release agent to a thickness of 1 mm. Underfill materials 1 to 19 were injected with a syringe and cured at 100°C for 5 hours to obtain a cured product.
[0139] <Measurement of glass transition temperature and elastic modulus> The glass transition temperature (Tg) and elastic modulus at 250°C of the obtained cured product were measured using a viscoelasticity measuring device (DMA7100, Hitachi) under tensile conditions (strain amplitude 10 μm, minimum tension 0 mN, tension gain 1.5, initial force amplitude 10 mN, 1 Hz) and evaluated according to the following criteria. ◎: Tg is 180℃ or higher ○: Tg is 160℃ or higher and less than 180℃ △: Tg is 140℃ or higher and less than 160℃ ×: Tg is less than 140°C ○: Elastic modulus is 1.0 GPa or more ×: Elastic modulus less than 1.0 Pa
[0140] <Measurement of cure shrinkage rate> The density of the underfill material before curing was measured using a dry automatic density meter (AccuPic II, Shimadzu Corporation). The density of the cured material was determined by Archimedes' method using a precision balance (XS225DUV, Medlar Toledo). The cure shrinkage was calculated from each density obtained using the following formula and evaluated according to the following criteria. Cure shrinkage rate = (density after curing - density before curing) / density after curing x 100 ○: Curing shrinkage rate is 1.0% or more ×: Curing shrinkage rate is less than 1.0%
[0141] <Measurement of average coefficient of linear thermal expansion (CTE)> The cured product was cut into test pieces with a width of 0.8 mm and a length of 15 mm, and a thermomechanical analysis was performed by the tensile load method using a thermomechanical analyzer (Hitachi High-Tech Science Corporation, TMA7100). After mounting the test piece on the device, it was measured twice consecutively under the measurement conditions of a load of 1 g and a heating rate of 5°C / min. The average linear thermal expansion coefficient (CTEα2: ppm) from Tg+40°C to 260°C in the second measurement was calculated and evaluated according to the following evaluation criteria. ◯: Average linear thermal expansion coefficient is less than 50 ppm △: Average linear thermal expansion coefficient is 50 ppm or more and less than 100 ppm ×: Average linear thermal expansion coefficient is 100 ppm or more
[0142] <Measurement of Volatility> 1 g of each of the underfill materials 1 to 19 was weighed out using a precision balance (XS225DUV, Medlar Toledo) into an aluminum cup and heated for 1 hour on a hot plate heated to 40°C. The weight of the sample after heating was measured using the precision balance, and the volatility was evaluated based on the rate of weight loss. ○: Weight loss rate is less than 4% △: Weight loss rate is 4% or more and less than 10% ×: Weight loss rate is 10% or more
[0143] <Filling test> A 100 μm thermosetting film (GX-92, manufactured by Ajinomoto Fine-Techno Co., Ltd.) was attached to the glass plate to form a spacer with a width of 1 cm and a height of 100 μm. The side of the thermosetting film opposite to the side in contact with the glass plate was covered with a glass plate, and the thermosetting film was cured to produce a test module with a gap of 100 μm. This test module was heated to 40°C on a hot plate, and underfill materials 1 to 18 were dropped with a syringe, and the length (mm) advanced in one minute was measured and evaluated according to the following criteria. Note that underfill material 19 had a high viscosity, so the length advanced in one minute could not be measured. 〇: Filling speed is 5mm / 1min or more ×: Filling speed is less than 5mm / 1min
[0144] Silicon wafer 3cm x 3cm: 900mm 2 The test module was cut to 40°C, and a thermosetting film (GX-92, manufactured by Ajinomoto Fine-Techno Co., Ltd.) measuring 2 mm x 2 mm was attached to each of the four corners to form a spacer with a height of 100 μm. The side of the thermosetting film opposite to the side in contact with the glass plate was covered with a glass plate, and the thermosetting film was cured to produce a test module with a gap of 100 μm. The test module was heated to 40°C on a hot plate, and underfill materials 1 to 15 were dropped onto one side with a syringe. The time required to complete filling (filling completion time) was measured and evaluated according to the following criteria. Note that underfill material 19 had a high viscosity, so it was not possible to fill the gap with underfill material 19. 〇: Charging completion time is less than 120 minutes ×: Filling completion time is 120 min or more
[0145] [Table 2]
[0146] In Examples 1 to 18, it was confirmed that even when components (D) to (G) were not contained, the results were similar to those of the above Examples, although to different degrees. [Explanation of symbols]
[0147] 1, 100, 200, 300, 400, 500 Semiconductor chip packages 10, 11, 12, 13, 14, 15 Circuit board 20, 21, 22, 23a, 23b, 24a, 24b, 25a, 25b Hardened underfill material 30, 31, 32, 33, 34, 35 Semiconductor chips 36 Laminate 37 Through silicon pillar 41, 42, 43, 44, 45, 46, 47, 48, 49 Bump 51 Sealing layer 61 Redistribution layer 71, 72 Beer Hall 80, 81 Silicon interposer S1 Semiconductor chip projected area S2 Projected area of the cured underfill material
Claims
1. (A) an epoxy resin having two or more epoxy groups in one molecule; (B) a compound having an ethylenically unsaturated group and a functional group capable of reacting with the epoxy group of the component (A), and (C) an inorganic filler; An underfill material, wherein the component (B) contains one or more selected from the group consisting of (meth)acrylic acid and (meth)acrylic anhydride.
2. 2. The underfill material according to claim 1, further comprising (D) a non-functional ethylenically unsaturated group-containing compound capable of reacting with component (A).
3. The underfill material described in claim 2, wherein component (D) contains one or more selected from phenoxyethylene glycol (meth)acrylate and styrene-based monomers.
4. (A) an epoxy resin having two or more epoxy groups in one molecule; (B) a compound having an ethylenically unsaturated group and a functional group capable of reacting with the epoxy group of the component (A), (C) an inorganic filler, and (D) An underfill material containing a non-functional ethylenically unsaturated group-containing compound capable of reacting with component (A), An underfill material, wherein the component (D) contains one or more selected from the group consisting of phenoxyethylene glycol (meth)acrylate and a styrene-based monomer.
5. An underfill material as described in claim 3 or 4, wherein the styrene-based monomer contains one or more selected from styrene, α-methylstyrene, 4-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methoxystyrene, p-t-butylstyrene, p-n-butylstyrene, and p-tert-butoxystyrene.
6. 5. The underfill material according to claim 2, wherein the content of component (D) is 10% by mass or more and 70% by mass or less, when the resin component in the underfill material is taken as 100% by mass.
7. 5. The underfill material according to claim 1, wherein the content of component (C) is 60% by mass or more, assuming the components of the underfill material to be 100% by mass.
8. The underfill material according to any one of claims 1 to 4, which has a viscosity at 40°C of 2000 mPa.s or less.
9. 5. The underfill material according to claim 1, wherein a molar ratio of all epoxy groups in component (A) to all functional groups in component (B) (total epoxy groups in component (A):total functional groups in component (B)) is in the range of 30:70 to 80:
20.
10. 5. The underfill material according to claim 4, wherein the functional group of component (B) capable of reacting with the epoxy group of component (A) is one or more groups selected from the group consisting of an epoxy group, an acid anhydride group, and a carboxyl group.
11. 5. The underfill material according to claim 1, wherein component (B) contains a compound having one or more epoxy groups and one or more ethylenically unsaturated groups in one molecule.
12. The underfill material according to any one of claims 1 to 4, wherein the component (B) contains glycidyl (meth)acrylate.
13. The underfill material according to any one of claims 1 to 4, further comprising (E) a radical polymerization catalyst.
14. The underfill material according to any one of claims 1 to 4, further comprising (F) an organic base.
15. The underfill material according to any one of claims 1 to 4, further comprising (G) an organic filler.
16. The underfill material according to any one of claims 1 to 4, wherein the average particle size of component (C) is 15 µm or less.
17. 5. The underfill material according to claim 1, wherein the cured product obtained by curing the underfill material has an elastic modulus of 1.0 GPa or more at 250°C.
18. 5. The underfill material according to claim 1, wherein a cured product obtained by curing the underfill material has a cure shrinkage rate of 1% or more.
19. The underfill material according to any one of claims 1 to 4, which is used to fill a gap between a circuit board and a semiconductor chip.
20. The underfill material according to any one of claims 1 to 4, which is used to fill a gap between a semiconductor chip and a rewiring layer.
21. The underfill material according to any one of claims 1 to 4, which is used to fill a gap between a circuit board and a rewiring layer.
22. 21. The underfill material of claim 20, wherein the redistribution layer comprises a polyimide.
23. The underfill material according to any one of claims 1 to 4, which is for use in a semiconductor device having a multi-die package.
24. The area of the semiconductor chip package is 900 mm 2 The underfill material according to any one of claims 1 to 4, which is for use in the above semiconductor device.
25. The underfill material according to any one of claims 1 to 4, which is for a semiconductor device including a fan-out type package.
26. The underfill material according to any one of claims 1 to 4, which is for a semiconductor device including a semiconductor package including a silicon interposer.
27. The underfill material according to any one of claims 1 to 4, which is for a semiconductor device including a stack in which two or more semiconductor chips are stacked vertically through through-silicon vias.
28. 20. The underfill material of claim 19, wherein the gap is 200 [mu]m or less.
29. 20. The underfill material of claim 19, wherein the gap is 100 [mu]m or less.
30. The underfill material according to any one of claims 2 to 4, comprising at least one component (D) having a viscosity at 25°C of 50 mPa.s or less.
31. The underfill material according to any one of claims 1 to 4, comprising at least one component (B) having a viscosity at 25°C of 50 mPa.s or less.
32. The underfill material according to any one of claims 1 to 4, which is an underfill material used in a post-coating method.
33. A semiconductor chip package comprising the cured underfill material according to any one of claims 1 to 4.
34. A semiconductor chip package comprising: a circuit board; a semiconductor chip bonded and mounted on the circuit board; and a cured product of the underfill material according to any one of claims 1 to 4, which fills a gap between the circuit board and the semiconductor chip.
35. 34. The semiconductor chip package of claim 33, wherein when a projected area of the semiconductor chip surface is S1 and a projected area of the cured underfill material is S2, (S2 / S1) x 100 is 120% or less.
36. 34. The semiconductor chip package of claim 33, wherein when a projected area of the semiconductor chip surface is S1 and a projected area of the cured underfill material is S2, (S2 / S1) x 100 is 110% or less.
37. 34. The semiconductor chip package of claim 33, wherein when a projected area of the semiconductor chip surface is S1 and a projected area of the cured underfill material is S2, (S2 / S1) x 100 is 105% or less.
38. 34. The semiconductor chip package of claim 33, wherein a cross-sectional shape of the cured underfill material decreases from the semiconductor chip toward the center of the cured material and increases from the center of the cured material toward the circuit board.
39. A method for manufacturing a semiconductor chip package, comprising the step of filling a gap between a circuit board and a semiconductor chip or an interposer with the underfill material according to any one of claims 1 to 4, The area of the semiconductor chip package or interposer is 900 mm 2 The method for manufacturing a semiconductor chip package as described above, wherein the time required to complete filling of the underfill material when the gap is 600 μm or less is less than 120 minutes.
40. A semiconductor device comprising the semiconductor chip package according to claim 33.
41. A cured product of the underfill material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Positive photosensitive resin composition, method for manufacturing semiconductor device and semiconductor device
JP2004093816A
Paste for mounting semiconductor device
JP2012142438A
Liquid epoxy resin composition for semiconductor encapsulation, and semiconductor device using the same
JP2013032522A
Liquid epoxy resin composition, and semiconductor device
JP2013189489A
Thermosetting resin composition with diene / dienophile pair and repairability
JP2016514738A